Implementasi Memorandum Of Understanding Antara Indonesia dan UNHCR dalam Perlindungan Pengungsi Asing di Indonesia: Suatu Analisis Normatif dalam Perspektif Hukum Perjanjian Internasional. - Hera Fitria Nuriana; Faisal Syafri Azmi (Jurnal Hukum Lex Generalis, 2026)
This research analyzes the legal status and implementation of the MoU in the practice of refugee management. The findings indicate that, formally, the MoU does not constitute a legally binding treaty under the Vienna Convention on the Law of Treaties 1969 and Law No. 24 of 2000 on International Agreements. Substantively, the implementation of the MoU has failed to transform human rights protection commitments. This failure is reflected in legal status uncertainty, inadequate accommodation facilities, and the dominance of an immigration security paradigm. The study ultimately demonstrates that the MoU represents a deliberate yet fragile policy choice, thereby necessitating reinforcement through more comprehensive national regulations to ensure the protection of refugees’ human rights.